2023
DOI: 10.1038/s41467-023-38581-8
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1-mediated RNA editing of SCD1 drives drug resistance and self-renewal in gastric cancer

Abstract: Targetable drivers governing 5-fluorouracil and cisplatin (5FU + CDDP) resistance remain elusive due to the paucity of physiologically and therapeutically relevant models. Here, we establish 5FU + CDDP resistant intestinal subtype GC patient-derived organoid lines. JAK/STAT signaling and its downstream, adenosine deaminases acting on RNA 1 (ADAR1), are shown to be concomitantly upregulated in the resistant lines. ADAR1 confers chemoresistance and self-renewal in an RNA editing-dependent manner. WES coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…These studies comprised 22 cohort studies [ 31 52 ]and 2 nested case-control studies [ 7 – 30 ]. In terms of patient sources, 15 studies originated from multicenter sources [ 31 , 33 – 35 , 37 , 39 , 40 , 42 , 44 48 , 50 , 51 , 53 ], 2 were drawn from a registered database [ 13 , 18 ], and 7 were conducted at single centers [ 8 , 10 , 15 , 20 , 23 , 27 , 30 ]. In a follow-up report, one study specifically focused on in-hospital deaths resulting from the combination of Talaromyces marneffei and HIV infection [ 8 ], while the remaining studies reported deaths during long-term follow-up, with the longest follow-up period extending to 36 years [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies comprised 22 cohort studies [ 31 52 ]and 2 nested case-control studies [ 7 – 30 ]. In terms of patient sources, 15 studies originated from multicenter sources [ 31 , 33 – 35 , 37 , 39 , 40 , 42 , 44 48 , 50 , 51 , 53 ], 2 were drawn from a registered database [ 13 , 18 ], and 7 were conducted at single centers [ 8 , 10 , 15 , 20 , 23 , 27 , 30 ]. In a follow-up report, one study specifically focused on in-hospital deaths resulting from the combination of Talaromyces marneffei and HIV infection [ 8 ], while the remaining studies reported deaths during long-term follow-up, with the longest follow-up period extending to 36 years [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The generation of the validation set involved internal random sampling and external validation, with external validation utilizing two modes: prospective and multicenter. The 8 studies employed survival analysis models (COX regression) [ 7 , 9 11 , 20 , 23 , 26 , 30 ], while the remaining 16 studies utilized non-survival analysis models [ 32 , 35 – 42 , 44 46 , 49 51 ]. The modeling variables are detailed in the Additional Materials.…”
Section: Resultsmentioning
confidence: 99%
“…Substituting A with I in an A-U base pair reduces stability, while introducing I in an A-C mismatch increases stability [ 63 ]. Wone et al demonstrated that A-to-I editing of the 3’ UTR of stearoyl-CoA desaturase (SCD1) increased KHDRBS1 binding, thus enhancing the stability of SCD1 mRNA [ 64 ]. Apart from ADAR1, ADAR2 also binds to and stabilizes RNA in a manner that is independent of editing.…”
Section: A-to-i Rna Editingmentioning
confidence: 99%
“…As mentioned above, RNA editing is correlated with the emergence of resistance [ 31 ] ; organoid lines from resistant patients with the intestinal subtype of gastric cancer (GC) showed upregulation of JAK/Src-signal transducer and activator of the transcription (STAT) signaling and adenosine deaminases acting on RNA 1 (ADAR1), along with hyper-edited lipid metabolism genes due to A-to-I editing on the 3’UTR of stearoyl- CoA desaturase (SCD1). SCD1 favored lipid droplet formation, reducing chemotherapy-induced ER stress and enhancing self-renewal in resistant GC lines [ 63 ] . In another subset of GC known as stem-like/Epithelial-to-mesenchymal transition/Mesenchymal (SEM-type) GC, resistance to glutaminolysis inhibition was observed due to a stem-like population in the tumor.…”
Section: Applications Of 3d Culture Systems In Drug Resistance Researchmentioning
confidence: 99%